Effects of socioeconomic status on the control of hypertension in patients <65 and ≥65 years of age in Taiwan: a nationwide cross-sectional study. Issue 2 (23rd February 2022) - Lin, Sheng-Feng; Kuo, Tzu-Tung; Pan, WH; Bai, Chyi Huey
Abstract : Objective: Implementation of National Health Insurance in 1995 improved the control of hypertension due to comprehensive coverage of medical costs for all residents in Taiwan. However, the role of individual socioeconomic status (iSES), namely, education and personal income, in awareness, treatmen, and control of blood pressure, has not been well studied in Taiwan. Design: A nationwide cross-sectional survey was executed in this study. Setting: A systematic, multistage sampling scheme from a nationwide cohort in Taiwan was adopted to select adult participants. Hypertension was defined as blood pressure ≥ 140/90 mm Hg or the use of antihypertensive medications. Participants: A total of 4599 subjects completed door-to-door household interviews and physical examinations. Primary and secondary outcome measures: A summing z score of iSES was constructed by two domains of the iSES, namely, income and education, through which participants were classified into three SES levels. Logistic regression models were used to assess associations of awareness, treatment, and control in younger (<65 years) and older (≥65 years) participants with hypertension. Results: Younger people in the highest tertile of iSES were less likely to be aware of their hypertension (OR: 0.48, 95% CI: 0.37 to 0.64, p<0.0001) or to have it treated (OR: 0.49, 95% CI 0.37 to 0.64, p<0.0001) but more likely to have their hypertension controlled (OR: 1.52, 95% CI 1.19 to 1.94, p=0.0009). We did not detect an association in people aged >65 years. Conclusion: Health education to improve awareness and treatment of hypertension should focus on younger people with higher iSES in Taiwan.